Analisis Kesalahan Siswa Dengan Tipe Berpikir Semikonseptual Berdasarkan Teori Nolthing - Christine Wulandari Suryaningrum; Ulul Iftha Frahnadya; Chusnul Khotimah Galatea (Universitas Islam Jember, 2023)
The purpose of this research is to describe students’ mistakes with semi-conceptual thinking types in solving mathematical problems in rectangular material. This type of research uses descriptive qualitative. Data collection techniques used written tests and semi-structured interviews. Subjects in class VIIE SMPN 7 Jember. Data analysis techniques use 3 ways, namely data reduction, data presentation, and drawing conclusions. The data validity technique uses the triangulation method. The results of this study are that many students make the same mistake due to a lack of reasoning ability to re-describe the information contained in the problem, and a lack of understanding of the concept so that dominant students just memorize concepts or formulas but cannot apply them to solve questions and do not check back answers to get answers. Correct result. Keywords: students’ error, semi-conceptual thinking type, Nolthing theory